Real-Time Telemedical Oversight Improves Prehospital Stroke Metrics: A Five-Year Cohort Study - Ponlawat Kanchayawong; Kasamon Aramvanitch; Chaiyaporn Yuksen; Satariya Trakulsrichai; Pungkava Sricharoen; Sureerat Suwatcharangkoon; Patcharaporn Sirintaranont; Jesada Keandoungchun; Promphet Nuanprom; Chetsadakon Jenpanitpong; Suthap Jaiboon (Archives of Academic Emergency Medicine)
Introduction: By enabling direct consultation with neurologists, Real-Time Telemedical Oversight (ReTMO) can facilitate rapid stroke assessment and decision-making. This study aimed to assess the efficacy of prehospital stroke management before and after ReTMO implementation.